Asset Mapping: A Tool to Enhance Your CSPAP Efforts. (4th March 2018) - Allar, Ishonté; Bulger, Sean
Abstract : Comprehensive school physical activity programs (CSPAPs) are one way to help students achieve most, if not all, of the recommended 60 minutes of daily moderate-to-vigorous physical activity (MVPA). Early in the process, one can use asset mapping to help enhance CSPAP efforts. Asset maps provide a valuable opportunity to identify potential partners in physical activity promotion, as well as disseminate knowledge of existing physical activity opportunities in the community. The purpose of this article is to provide a description of asset mapping and the related methods that teachers can use during the process.